Enhanced electrochemical performances of LiNi0.5Mn1.5O4 by surface modification with Cu nanoparticles - zhao Guiying; Lin Yinbin; Zhu Weibo; Yang Wenyu; Huang Zhigao (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
5V spinel LiNi0.5Mn1.5O4 cathode is prepared by traditional solid-state method and nano-Cu particles were derived from a chemical reduction process. The effect of Cu-coating on the electrochemical performances of LiNi0.5Mn1.5O4 cells, in a wide operation temperature range (-10℃, 25℃,60℃), is investigated systematically by the charge/discharge testing, cyclic voltammograms and impedance spectroscopy, respectively. The results of electrochemical experiments demonstrate that the modified material exhibits remarkably enhanced electrochemical reversibility and stability in a wide operation temperature range. Cu-coated material has much lower surface and charge-transfer resistances and shows a higher lithium diffusion rate. The Cu coating layer as a highly efficient lithium ion conductor, protected the surface of the active materials from HF generated by the decomposition of LiPF6 in the electrolyte during electrochemical cycling and acted as a highly efficient protector to restrain the contact loss.